Clinical characteristics of nephrocalcinosis in a tertiary children's hospital - Zheng, Jiajia; Cao, Jie; Chen, Lan; Xia, Xuhua (Frontiers in Pediatrics, 2025)
BackgroundNephrocalcinosis (NC) is often associated with prematurity, genetic, and/or metabolic disorders. However, studies focusing on NC in pediatric population remain limited.AimsThis study aimed to explore the etiology of NC and characterize clinical manifestation in children.MethodsWe retrospectively reviewed the electronic medical records of consecutive 50 children diagnosed with NC between January 1, 2016, and December 31, 2022, at the Children's Hospital of Chongqing Medical University. The data were analyzed to determine the underlying causes and clinical presentations of NC.ResultsOf the 50 children diagnosed with NC, 50% were younger than 2 years old. Congenital diseases were diagnosed in 54% of the children, with renal tubular acidosis (RTA) accounting for 44% of these cases. Genetic testing confirmed diagnoses in 45% of cases (10 out of 22 tested). Although NC often presents with non-specific and diverse symptoms, 18% of the children were asymptomatic. During a long-term follow-up, 69% of cases showed no signs of improvement and 2 patients later developed nephrolithiasis. Only 13% suffered from impaired renal function and one of them developed into chronic kidney disease.ConclusionsCongenital or genetic disorders are the primary causes of NC in children. Most cases persist overtime, underscoring the need for early identification of underlying causes through genetic testing and the development of more effective treatments for NC. While most children maintained normal renal function, the relationship between NC and renal functional decline warrants further investigation.